The Role of Calcium in the Skin Barrier - Nopriyati; Ahmad Ligar Suherman; Yulia Farida Yahya; Mutia Devi (HM Publisher, 2022)
Calcium is a macro mineral that is an important part of the body. Bones and teeth contain more than 99% of the human body calcium. Calcium also found in other tissues such as skin. The concentration of calcium in the body tends to decrease with age because released from the body through sweat, skin cells, and faeces. Calcium intake varies worldwide with an average of 175-1233 mg/day. Many countries in Asia have an average calcium intake of less than 500 mg/day. The skin barrier function is in the epidermis, the formation of the epidermal barrier and the maintenance of homeostasis are important to protect the individual from the external environment and organisms. Epidermal calcium gradient, endoplasmic reticulum (ER) calcium homeostasis, and calcium influx through calcium channels play important roles in keratinocyte differentiation, barrier formation, and barrier homeostasis. Understanding the mechanism of regulation and function of calcium related to skin barrier homeostasis is aimed to improve understanding of calcium in the skin barrier